Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

AMP1-1 derived from Atractylodes macrocephala Koidz prevents bone aging triggered by lead and cadmium - Jinpeng Wang; Yu Jiang; Xiaoyu Hou; Tahir Raza; Yiping He; Xinyue Liu; Defeng Xing; Lijun Wei (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Experimental study on shear performance of prefabricated HSS-UHPC composite beam with perfobond strip connectors - Shaohua He; Defeng Zhou; Baisheng Bai; Changxi Liu; You Dong (Engineering Structures, 2025)

Fluorocarbon polymers mediated contact-electro-catalysis activating peroxymonosulfate for emerging pollutants degradation: The key role of fluorine density in electron transfer - Dongmei Ma; Wei Li; Jin Zhang; Kuanchang He; Changyong Zhang; Gang Wang; Xiaodong Xin; Qian Liu; Faliang Cheng; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2024)

Efficient removal of hexavalent chromium from wastewater using a novel sodium alginate-biochar composite adsorbent - Yushi Tian; Xiaolin Sun; Nianhua Chen; Xintong Cui; Hui Yu; Yujie Feng; Defeng Xing; Weihua He (Journal of Water Process Engineering, 2024)

Dating Kimberlite Using Apatite U-Pb Geochronology: A Case Study from Diamond-Bearing Dikes in South China - Jiawei Zhang; Huan Wang; Defeng He; Yuhua Zhu; Kun Wang; Yuan Qiu (Journal of Earth Science, 2024)

Flexural behavior and design methodology for bamboo scrimber-aluminum plate composite beams - Ye Sheng; Defeng Tu; Feiyu Liao; Yuxing Yang; Chenggen He; Wei Zhang; Cheng Meng (Engineering Structures, 2023)

Carbon-based materials as highly efficient catalysts for the hydrogen evolution reaction in microbial electrolysis cells: Mechanisms, methods, and perspectives - Lina Xu; Wei Li; Jiaqin Luo; Lingyu Chen; Kuanchang He; Dongmei Ma; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2023)

Streptococcus shenyangsis sp. nov., a New Species Isolated from the Oropharynx of a Healthy Child from Shenyang China - Defeng Liu; Chunling Xiao; Xinming Li; Ye Sun; He Qi; Yang Zou (Current Microbiology, 2021)

Description and genomic characterization of Streptococcus symci sp. nov., isolated from a child’s oropharynx - He Qi; Defeng Liu; Yang Zou; Nan Wang; Han Tian; Chunling Xiao (Antonie van Leeuwenhoek, 2021)
Using the culturomics approach, we isolated a new Streptococcus species, strain C17 T , from the oropharynx mucosa sample of a healthy 5-year-old child living in Shenyang, China. We studied the phenotypic, phylogenetic, and genomic characteristics of strain C17 T , which was identified as a Gram-positive, coccus-shaped, non-motile, aerobic, catalase-negative bacteria. Its growth temperatures ranged from 20 to 42 °C, with optimal growth at 37 °C. Acid production could be inhibited by two sugars, trehalose and raffinose. In C17 T , the reactions for enzyme lipase (C14) were confirmed to be negative, whereas those for alkaline phosphatase, α-glucosidase, and hippuric acid hydrolysis were positive. The C17 T genome contained 2,189,419 base pairs (bp), with an average G+C content of 39.95%, encoding 2092 genes in total. The 16S ribosomal RNA sequence showed 99.8% similarity with the newly identified Streptococcus pseudopneumoniae ATCC BAA-960 T . The main fatty acid components in C17 T were C16:0, C18:1 w7c, C18:0, and C18:1 w9c, all of which can be found in other species of the Streptococcus genus. Strain C17 T showed high susceptibility to clindamycin, linezolid, vancomycin, chloramphenicol, and cefepime, and moderate susceptibility to erythromycin. The obtained dDDH value between strain C17 T and the closest species was 52.9%. In addition, the whole genome sequence of strain C17 T had an 82.21–93.40% average nucleotide identity (ANI) with those strains of closely related Streptococcus species, indicating that the strain C17 T was unique among all Streptococcus species. Based on these characteristics, we determine that C17 T is a novel species, named Streptococcus symci sp. nov. (= GDMCC 1.1633 = JCM 33582).

The performance of the Noblesse multi-collector noble gas mass spectrometer for 40Ar/39Ar geochronology - Defeng He; Finlay M. Stuart; Dan N. Barfod; Fang Xiao; Hong Zhong (Acta Geochimica, 2018)

The structural characteristics, age of origin, and tectonic attribute of the Erguna Fault, NE China - Han Zheng; XiaoMeng Sun; DeFeng Zhu; JingXiong Tian; Song He; YingDe Wang; XuQing Zhang (Science China Earth Sciences, 2015)